Treated wastewater as a partial nutrient source for Lily grown in a soilless system in presence of Arbuscular Mycorrhizal Fungi - Ibrahim Makhadmeh; Khaled Abu Rashed; Ammar A Albalasmeh (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The reuse of treated wastewater (TWW) in agriculture may affect the growth of plants. The goal of this study is to investigate the potential use of TWW in irrigating Lily in presence of Arbuscular Mycorrhizal Fungi (AMF) in a closed soilless system.Method In the first experiment, plants were irrigated with a mixture of 3 part nutrient solution: 1 part treated wastewater (3NS:1TWW) supplemented with 50, 125, 160 or 200 mg L-1 Ca to determine the optimal Ca concentration supplement that would give the highest plant growth. In the second experiment, the plants were irrigated with a nutrient solution or a mixture of 3 part nutrient solution: 1part treated wastewater (3NS:1TWW) supplemented with 160 mg L-1 Ca in the presence or absence of AMF.Results The results indicated that the plants receiving the higher concentrations of Ca (160 or 200 mg L-1) showed better growth performance. The results showed that the plants receiving (3NS:1TWW) had a significantly higher dry weight of adventitious roots and fresh weight of the flower bud than those receiving nutrient solution. The flower bud was longer in presence of AMF. The highest shoot fresh weight was recorded for non-AMF plants receiving 3NS:1TWW, and the least shoot fresh weight.Conclusion The most efficient solution is to supplement the 3NS:1TWW irrigation solution with 160 mg Ca L-1 to reduce the salinity effects of TWW. Moreover, it is recommended to inoculate the roots of the Asiatic lily plants with AMF to achieve the longest flower.